Adenosinergic control of fear extinction: the role of adenosine A2A receptors in the basolateral amygdala - Lourenço, Vanessa Simões (2019)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia